Понятие „конфликтная компетентность” и ее составляющие [Articol] - Анцибор, Людмила; Серафимчук, Павел (My University, 2021)
в работе рассмотрены основные подходы к пониманию понятия «конфликтная компетентность», а также проведен обзор степени изученности конфликтной компетентности выделяя ее составляющие. выделены признаки конфликтной компетентности через стили поведения в конфликте и через принципы управления конфликтом.

The article considers the main approaches to understanding of concepts of conflict competence, review of the degree of knowledge of conflict competence and consideration of conflict competence through the selection of its components. Features of conflict competence are highlighted through styles of behavior in conflict and principles of conflict management.

În lucrare sunt luate în atenție principalele abordări ale conceptului de competență conflictială, prin specificarea componentelor sale, fiind revizuit gradul de studiere a competenței conflictuale. Semnele competenței conflictuale sunt evidențiate prin stilurile de comportament în conflict și prin principiile managementului conflictelor.
CONCEPT OF CONFLICT COMPETENCE, AND THE SELECTION OF ITS COMPONENTS
Keywords: конфликт; сonflict; конфликтная компетентность